TEACHING TECHNOLOGIES OF FOLK CRAFTS FOR STUDENTS - Esanova Sarvinoz Uktamovna (Modern American Journals, 2025)
This article explores modern pedagogical technologies used in teaching folk crafts to students in higher and secondary special education institutions. The study emphasizes the significance of integrating national heritage into the educational process to develop students’ professional, creative, and social competencies. Special attention is given to the role of folk crafts in fostering cultural identity, work ethics, and artistic expression among youth.
Keywords: Folk crafts, teaching technologies, students, cultural heritage, social competencies, professional education, applied arts, creative development, traditional skills, pedagogical methods.